Developing an argumentative writing scale - Nimehchisalem, Vahid; Mukundan, Jayakaran; Rafik Galea, Shameem (Universiti Putra Malaysia Press, 2012)
Today, with more emphasis on the student writers’ awareness of the genres of writing, there is a need for writing scales that are sensitive to the variation in the text types. Numerous writing scales have been developed over the past decades, but new scales are required to be developed as the testing situations vary. As a part of a project that aimed at developing a genre-specific writing scale to evaluate tertiary level argumentative writing, a focus group study was conducted. For this purpose, a pre-existing group of experienced English as a Second Language (ESL) lecturers (n=4) discussed what traits of the argumentative writing skill should be included in a writing scale. They also discussed how much weight should be assigned to each trait. As a result of the study, the subscales of ‘task fulfilment’, ‘content’, ‘organization’, ‘vocabulary’, ‘style’, ‘grammar’ and ‘mechanics’ (in the order of their importance) were proposed by these experts. The study has implications for teaching-testing of ESL writing skill.